Utilizing Concept Maps to Uncover Misconceptions in Human Reproductive System Material - Awanda Febriana Kusumawardani; Meiry Fadilah Noor; Sulhah Amaliyah (Department of Biology Education UIN Sunan Gunung Djati Bandung, 2025)
Misunderstanding concepts in Biology learning can hinder the process of knowledge reception and assimilation in students, potentially impeding their academic achievement. This study aims to explore student misconceptions using concept maps. The research was conducted at MAN 1 Tangerang Selatan (State Islamic High School 1 South Tangerang) in October 2022. The material used to explore misconceptions was the human reproductive system, which students had previously studied. A qualitative descriptive method was employed in this study. Purposive sampling was used as the sampling technique. Data were collected using the Student Worksheet for Concept Map Compilation and Creation instrument, which contained instructions for creating concept maps, preceded by an explanation of concept maps, their characteristics, examples, and steps for creating them. Clarification interviews were also conducted to clarify misconceptions revealed in the students' concept maps. Student concept map answers were analyzed based on categories of knowing concepts, misconceptions, and not knowing concepts. The results from the concept map creation test and clarification interviews showed that students experienced misconceptions regarding human reproductive organ concepts, gametogenesis, fertilization, pregnancy, menstruation, and breastfeeding. Students exhibited the most misconceptions regarding the concept of Fertilization. Thus, concept maps can be used as an evaluation tool for misconceptions experienced by students